Discourse Construction on the Appointment of SPPG Employees to PPPK in Online Media Reporting: A Critical Discourse Analysis of Teun A. van Dijk's Model - Ramdan Gumilar; Deasy Aditya Damayanti; Ninah Hasanah; Agus Ha; Ari Kartini (Papanda Publisher, 2026)
Online media plays a crucial role in conveying and explaining public policy to the public. This study aims to examine how Liputan6.com presents the discourse on the appointment of Nutrition Fulfillment Service Unit (SPPG) employees to Government Employees with Work Agreements (PPPK) in the Free Nutritional Meal Program (MBG). This study uses a descriptive qualitative approach with Teun A. van Dijk's Critical Discourse Analysis method, which includes analysis of text structure, social cognition, and social context. The research data consists of a Liputan6.com news text entitled